The role of the Bidayuh community in packaging culture and nature for sustainable indigenous tourism product in Bau District, Sarawak - Johari, Shazali; Ramachandran, Sridar; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman; Kunasekaran, Puvaneswaran (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
This paper aims to explore the unique cultural attributes owned by the Bidayuh community. In addition, the existing natural products and its utilization for tourism sustainability is also captured. The tourism sustainability is measured from main three dimensions; economic, sociocultural and environmental sustainability. This study employs qualitative approach. The data is collected using initial inquiry technique aiming at induction of knowledge in the relevant field of community development and tourism. Apart from that, this study also reveals the readiness of the native community to involve in tourism business and challenges faced by them to develop tourism in their area. The cultural uniqueness of the community is recognized by both the international tourists and the other Malaysian communities. However, the development of tourism to expose the culture of the community to outsiders is still questionable. The preliminary data shows that the community is very proud with their culture and surrounding nature. They are willing to share their uniqueness to the outsiders. However, lesser contribution and support from other stakeholders makes their effort slow and diminished. Thus this study is important to create awareness to outsiders about the unexplored indigenous resources to amplify their uniqueness without destroying it by commodification.